UI/UX Design Analysis of Students' Integrated Information System Using Design Thinking and Agile Scrum with System Usability Scale (SUS) Evaluation in Jayawijaya District - Haris Asso; Kristiawan Nugroho (Politeknik Pertanian Negeri Samarinda, 2026)
Student scholarship management in Jayawijaya Regency still faces various challenges, including non-integrated data management, administrative processes that are still performed manually, low transparency, and ineffective coordination among stakeholders. These conditions result in delays in scholarship distribution, difficulties in monitoring and decision-making that is not yet supported by integrated data. This study aims to design and evaluate an Integrated Student Information System to support scholarship management by applying the Design Thinking approach combined with the Agile Scrum development framework. The Design Thinking process was used to identify stakeholder needs, formulate system requirements, and generate solution concepts, which were subsequently translated into nine Product Backlog items to be developed incrementally through three development sprints. The resulting prototype includes multi-role authentication, student dashboard, Education Office dashboard, online scholarship application, verification and validation, application status tracking, student data management, communication and notification, and reporting. The prototype was subsequently evaluated using the System Usability Scale involving 41 respondents. The evaluation results produced an average score of 74.39, indicating that the prototype falls within the Acceptable category with good usability. The findings demonstrate that the integration of Design Thinking and Agile Scrum is capable of producing a user-centered prototype, improving transparency, coordination and supporting the digital transformation of scholarship management in Jayawijaya Regency.